Infections and Multiple Sclerosis: From the World to Sardinia, From Sardinia to the World - Frau, Jessica; Coghe, Giancarlo; Lorefice, Lorena; Fenu, Giuseppe; Cocco, Eleonora (Frontiers in Immunology, 2021)
Multiple Sclerosis (MS) is an inflammatory disease of the central nervous system. Sardinia, an Italian island, is one of the areas with the highest global prevalence of MS. Genetic factors have been widely explored to explain this greater prevalence among some populations; the genetic makeup of the Sardinians appears to make them more likely to develop autoimmune diseases. A strong association between MS and some infections have been reported globally. The most robust evidence indicating the role of infections is MS development concerns the Epstein-Barr virus (EBV). Anti-EBV antibodies in patients once infected by EBV are associated with the development of MS years later. These features have also been noted in Sardinian patients with MS. Many groups have found an increased expression of the Human endogenous retroviruses (HERV) family in patients with MS. A role in pathogenesis, prognosis, and prediction of treatment response has been proposed for HERV. A European multi-centre study has shown that their presence was variable among populations, ranging from 59% to 100% of patients, with higher HERV expression noted in Sardinian patients with MS. The mycobacterium avium subspecies paratuberculosis (MAP) DNA and antibodies against MAP2694 protein were found to be associated with MS in Sardinian patients. More recently, this association has also been reported in Japanese patients with MS. In this study, we analysed the role of infectious factors in Sardinian patients with MS and compared it with the findings reported in other populations.